AMALAN PENGAJARAN PENSYARAH TAHFIZ AL-QURAN DI MALAYSIA: TEACHING PRACTICE AMONG TAHFIZ AL-QURAN LECTURER IN MALAYSIA - Abdul Rahim, Mohamad Marzuqi; Yussuf, Ahmad; Borham, Abd Hadi; Kamarul Zaman, Muhammad Akramin (Journal of Islamic Educational Research, 2016)
This study was aimed to unveil the perception of lecturers and employers of the lecturers’ teaching practices at Malaysia Tahfiz al-Quran Institution or "Maahad Tahfiz al-Quran Malaysia". This study involved 177 lecturers as samples, and 6 employers from selected maahad tahfiz. To achieve the study’s objective, a set of questionnaires with 10 items was used as an instrument to measure the lecturer’s perception towards teaching practice, while a semi-structured interviews containing 3 questions were used to obtain the views of employers regarding their role. The findings from questionnaire were analyzed descriptively and show as a whole, the level of lecturer’s teaching practice is moderate, with the mean value of 3.69. On the other hand, the results of interviews show that there is a difference in opinion between lecturers and employers in the aspect of diversifying the methods of teaching. Meanwhile the results of the study disclose a significant difference in the level of teaching practices of lecturers, based on academic qualifications, where lecturers holding degrees and higher level will lead to a higher perception (mean=3.74). The implication of this study concludes that teaching practices of lecturers should be enhanced in order to excel the al-Quran memorization education in Malaysia.